(Table, page 49) The composition of soil manganese concretions from Oahu Island, Hawaii - Kelley, WP (Supplement to: Kelley, WP (1912): The function and distribution of manganese in plants and soils. Bulletin (Hawaii Agricultural Experiment Station), 26, 56 pp, hdl:10125/25521, 1912)
The island of Oahu is made up of two almost parallel mountain ranges, the Koolau on the east and the Waianae on the west, with a sloping plateau of about 10 miles in width and 40 miles in length between these. This plateau comprises the principal portion of the arable land of Oahu. From the evidences at hand, the soil and deeper-lying disintegration products have resulted principally from the primary decomposition of normal basalt, under the influence of the usual weathering agencies incident to a humid subtropical climate. At intervals in this upland plain, there are areas which contain large quantities of manganese. Manganese concretions occur throughout the manganiferous soils of Oahu. Their chemical composition is similar to that of the manganese nodules found in the deep sea around the Hawaiian island during the Challenger expedition.